2010
DOI: 10.1096/fasebj.24.1_supplement.604.16
|View full text |Cite
|
Sign up to set email alerts
|

A role of the novel, non‐AT1, non‐AT2 angiotensin binding site in neuronal cell death

Abstract: The novel, non‐AT1, non‐AT2 angiotensin binding site is a yet unknown protein found in rodent and human brain membranes with pharmacological specificity and tissue distribution different from the type 1 and 2 angiotensin receptors and key enzymes involved in proteolytic processing of angiotensins. Here we report a summary of our recent studies indicating a correlation between the density of the novel binding site in primary neurons and neuronal cell death. 125I‐Sar1, Ile8 angiotensin II binding studies were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…7 Peptidase neurolysin (Nln), a zinc metallopeptidase, has been recognized as a key constituent of an endogenous cerebroprotective mechanism functioning to protect the brain in acute neurodegenerative disorders. 8,9 This notion is based on a series of recent in vitro and in vivo experimental studies which revealed upregulation of Nln following cerebral ischemia 10,11 and suggested its potential protective role in response of the brain to stroke. The functional significance of Nln in the poststroke brain has been previously established using a mouse ischemic stroke model which documented aggravation of disease outcomes following small molecule inhibition of Nln after stroke.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Peptidase neurolysin (Nln), a zinc metallopeptidase, has been recognized as a key constituent of an endogenous cerebroprotective mechanism functioning to protect the brain in acute neurodegenerative disorders. 8,9 This notion is based on a series of recent in vitro and in vivo experimental studies which revealed upregulation of Nln following cerebral ischemia 10,11 and suggested its potential protective role in response of the brain to stroke. The functional significance of Nln in the poststroke brain has been previously established using a mouse ischemic stroke model which documented aggravation of disease outcomes following small molecule inhibition of Nln after stroke.…”
Section: ■ Introductionmentioning
confidence: 99%